Experimental study on composite insulation with foam, multilayer and vapor cooled shield for cryogen storage under different vacuum conditions. (January 2023) - Jiang, Wenbing; Yang, Yilun; Hu, Cong; Li, Peng; Sun, Peijie; Huang, Yonghua
Highlights: An experimental setup for evaluating VCS has been established. 200–350 K boundary temperature and 10 −5 –10 5 Pa pressure were covered. VCS insulation performance decreases with increasing pressure. VCS reduces heat leakage into a LN2 vessel by 19.66% and 0.34% at 9.8 × 10 −5 Pa and 1.0 × 10 5 Pa, respectively. Abstract: The composite insulation composed of polyurethane foam (Foam), vapor cooled shield (VCS) and multi-layer material (MLI) can effectively reduce the heat leakage into the ground cryogenic vessels and space-used cryogenic containers throughout their whole life cycle. To comparatively evaluate the thermal performance of the MLI-VCS and the Foam-MLI-VCS combinations, an experimental setup has been designed and fabricated based on the evaporation calorimetry. It allows control of the warm boundary temperature between 150 K and 400 K and the environmental pressure in a wide range of 10 −5 –10 5 Pa. With the help of this facility, the thermal performance of the target insulation structures was evaluated at various warm boundary temperatures and different vacuum pressures. The temperature profiles and heat flux in the insulation were obtained. The results indicated that the heat fluxes into the liquid nitrogen vessel decreased by approximately 11.7% and 19.7% after installing a VCS when the warm boundary temperatures were 223.3 K and 332.4 K, respectively. Besides, the contribution to the overall performance by the VCS gradually decreases with the deterioration of the vacuum pressure. Under high vacuum (9.8 × 10 −5 Pa) conditions, VCS reduces the heat leakage into a liquid nitrogen container by 19.7% while it drops to merely 0.3% under atmospheric pressure (1.0 × 10 5 Pa). The results will be beneficial to the VCS-related thermal design.